The Influence of Income Level and Shopping Motivation on Impulsive Buying with Lifestyle as an Intervening Variable - Nurhidayatullah Rahma; Muzdalifah Muhammadun; Ahmad Dzul Ilmi Syarifuddin; Damirah; Andi Ayu Frihatni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the influence of income level and shopping motivation on impulsive buying with lifestyle as an intervening variable in postgraduate students of IAIN Parepare. The research method used is quantitative with an associative approach. The sample consisted of 99 respondents selected through purposive sampling technique. Data analysis was conducted using Partial Least Square (SmartPLS) to test the validity, reliability, and relationships between variables. The results showed that income level and shopping motivation have a positive and significant effect on impulsive buying, both directly and indirectly through lifestyle. Lifestyle is proven to be a mediator that strengthens the relationship between income level and shopping motivation on impulsive buying. Thus, the higher a person's income and shopping motivation, the greater their tendency to behave consumptively, especially if driven by a hedonic lifestyle oriented towards pleasure and trends.